2020
DOI: 10.21831/pep.v24i1.28815
|View full text |Cite
|
Sign up to set email alerts
|

Developing a dynamic assessment instrument to assess reasoning skills about bacteria

Abstract: This study was aimed to develop instruments to assess reasoning skills in the form of dynamic assessment as a formative assessment to improve students’ reasoning skills about bacteria. The cake format and graduated prompting method was used in this study. The instruments were based on the Fact and Proof Diagnostic Test and Structural Communication Grid (SCG) and focused on the correlational reasoning and combinatorial reasoning. The development of the instrument was carried out by compiling test items accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The finding of determining the unidimensional assumption is difficult to fulfill due to the discovery of several new factors that are also measured in one instrument (Khasanah et al, 2020;Kiklhorn et al, 2020). In other words, researchers often use psychological instruments to be multi-dimensional (Abubakar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of determining the unidimensional assumption is difficult to fulfill due to the discovery of several new factors that are also measured in one instrument (Khasanah et al, 2020;Kiklhorn et al, 2020). In other words, researchers often use psychological instruments to be multi-dimensional (Abubakar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, researchers often use psychological instruments to be multi-dimensional (Abubakar et al, 2022). The high tendency for measurement instruments to be multidimensional is caused by several things, including the characteristics of psychological constructs that tend to lead to multidimensional models, the involvement of aspects in the preparation of measuring multidimensional instruments, the number of items in the instrument being too large, the technique of writing items that have a positive direction (favorable) and negative (unfavorable), and different units of measurement (Khasanah et al, 2020). The results of calculating the reliability of the unidimensional student creativity questionnaire after removing items in the drop category were obtained using the alpha-Cronbach formula.…”
Section: Discussionmentioning
confidence: 99%
“…ere is a CA intervention that can be very helpful for students to perform better. e student thinking process to get the correct answer can be observed via CA [31]. e CA fundamentally supports the idea that assessment is also part of teaching and learning which can only be achieved through constant collaboration between teachers and students.…”
Section: Collaborative Assessment (As a Form Of E-assessment)mentioning
confidence: 92%
“…It indicated that the items were valid. Further, a reliability test was conducted using that generated value of 0.25 > 0.21 which means that the instrument was reliable (Khasanah, Ramli, & Dwiastuti, 2020).…”
Section: Instrumentmentioning
confidence: 99%